Analysis of Degung Sunda by Nining Meida (1988): Lexical Meaning, Contextual Meaning, and Figurative Language - Raisya Octavia Nurjannah; Otong Setiawan Djuharie; Andang Saehu (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
Traditional and regional songs play an important role in preserving language and cultural values. In Sundanese culture, popular songs function not only as entertainment but also as a medium for transmitting linguistic and cultural heritage. This study analyzes the linguistic elements of ten lyrical excerpts from Sundanese pop songs popularized by Nining Meida in 1988 through lexical meaning, contextual meaning, and figurative language. Using a qualitative method with content analysis, the study finds that the lyrics contain a rich vocabulary of romance and daily Sundanese life. The meanings are often symbolic and contextual, making literal interpretation difficult. Dominant figurative devices include metaphor, hyperbole, personification, and visual imagery. The findings indicate that these popular songs contribute significantly to preserving the Sundanese language and strengthening cultural identity.